Romantismo, esporte e cinema: Bobby Jones - A lenda do Golfe - Luciana Marins Nogueira Peil; Hugo Rodolfo Lovisolo (Universidade Federal do Rio Grande do Sul, 2010)
This text is based on the hypothesis that in the representation of sport the main assumptions and categories of Romanticism form its dominant narratives. The Romanticism used the language not only to talk about sport but also to generate feelings about it. In this case, we will take this particular narrative of the movie "Bobby Jones - Stroke of Genius" in order to locate and interpretate the assumptions and cores of the romantic conception. In Bobby Jones's filmed biography the basic aspects of Romanticism such as the notion of the Genius; the anguish of the division; the importance given to pleasure; the search for unity; the authenticity and the high value put on nature as well as its organic aspect are presented organizing the narrative. The movie develops its ideas from the perspective of enchanting the world again by setting a higher value on aspects of sensibility rather than on utilitarian ones. Sport, Golf especially in this case, presents itself as the greatest means as well as the greatest end of our whole realization as human beings, in patterns that are familiar to Romanticism.